Rational Dissent, Unitarianism, and the Closure of the Northampton Academy in 1798*. (23rd March 2016) - Wykes, David L.
Abstract : The decision by the Coward Trustees to close their academy at Northampton in June 1798 has generally been attributed to the prevalence of Unitarianism amongst the students. The reasons are more complex. Neither John Horsey, the theological tutor, nor the students at the time of the closure were Unitarian, though the latter were probably not Calvinists either. The appointment of David Savile, a zealous Calvinist, as assistant tutor by the trustees was a poor choice and led directly to the end of the academy. Closer investigation shows that the trustees differed little in their religious opinions from either Horsey or the students. The closure of the academy at Northampton can be used to identify the growing tensions within rational dissent as a result of the emergence of a more militant Unitarianism. It also proved to have extremely serious consequences for the future training of ministers for liberal dissent